2016
DOI: 10.5539/elt.v9n8p231
|View full text |Cite
|
Sign up to set email alerts
|

The Problems of Applying Student Centered Syllabus of English in Vocational High Schools in Kendal Regency

Abstract: This study was descriptive qualitative study aimed to investigate the problems of applying student centered syllabus in vocational high schools in Kendal regency, Central Java, Indonesia. The subjects of the study were twenty English teacher in vocational high schools in Kendal. The data were collected through observations, questionnaires, and interviews. The collected data further were analyzed using inductive analysis in which the researchers looked for the pattern of the data and the meaning of the data. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…The teaching materials used in EFL classrooms in Islamic higher education tend to use foreign cultures that are inappropriate for Islamic and Indonesian cultures. The results of this study harmonized with the research findings by Faridi et al (2016) and Cahyo et al (2019). Despite Nurfitriani et al (2018) had developed thematic teaching material based on local wisdom for elementary school students, Van Van (2016), Syed et al (2019), and Usadiati and Norahmi, (2019) had developed thematic teaching material based on local wisdom for junior high school students, they were found to have limited Islamicintegrated reading materials and lack the Indonesian culture.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The teaching materials used in EFL classrooms in Islamic higher education tend to use foreign cultures that are inappropriate for Islamic and Indonesian cultures. The results of this study harmonized with the research findings by Faridi et al (2016) and Cahyo et al (2019). Despite Nurfitriani et al (2018) had developed thematic teaching material based on local wisdom for elementary school students, Van Van (2016), Syed et al (2019), and Usadiati and Norahmi, (2019) had developed thematic teaching material based on local wisdom for junior high school students, they were found to have limited Islamicintegrated reading materials and lack the Indonesian culture.…”
Section: Discussionsupporting
confidence: 81%
“…Besides, the pictures in the book are not relevant to the Islamic cultural context. It was found that the teaching materials often showed native English speaker's pictures and those were inappropriate for Islamic schools in terms of clothes usage (Ariyanto, 2018;Faridi et al, 2016). The pictures in general English teaching material often exploited women's bodies as they wear short clothes which are not acceptable for Islamic school based on the akhlak (the practice of virtue, morality, and manners in Islamic theology and philosophy).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects' direct involvement in researching for the materials, in discussing with their peers and teacher, and also in teaching the materials with their own chosen methods has helped subjects' comprehension on the subject matter.Through teaching, subjects understand the materials more thoroughly as also mentioned by Ahmed [6]. Subjects' better comprehension on the materialshas also been the result of their being given a chance to discuss the materials as also stated by Kemberas cited in [8]. Post-test However, this study was conducted with some limitations too.…”
Section: Control Groupmentioning
confidence: 91%
“…As English was perceived very important for students both in their academic studies and future careers Nurakhir & Palupi, (2018), it is then important for both students and teachers to work cooperatively to deal with this issue. The way the students learn and increase their literacy will be very much influenced by the teaching and learning process in which the students are involved; therefore, as educators, teachers play an important role to make the learning meaningful, interesting, creative, dynamic, and interactive (Faridi et al, 2016).…”
Section: Socio-cultural Dimension Of Literacy In Students' Textsmentioning
confidence: 99%